(untitled) (Ciudades, 2017)
The goal of this article is to address the question of the variability and flexibility in the historical centers, analyzing the activities of two case studies in Europe: Salamanca and Stockholm. Both of them are clear examples of good adaptability and evolution of the fabric in a contemporary context and the result of very different urban policies. Stockholm is more radical and visionary, working by "selective destruction”, removing the unnecessary and not adaptable to create a more livable city. Salamanca’s strategy is more conservative and runs by "hybridization". It mixes the old and the new, conscious of the value of history and culture, and finds a way to give a new meaning. Both strategies involve the rejection of an obsolete "living museum" and therefore an approach to a better quality of their centers, using propelling tools, not pathological, which improve their urbanization process.